ANALISIS KETERAMPILAN DASAR MENGAJAR GURU PADA PROSES PEMBELAJARAN IPA KELAS V SDN 11 KECAMATAN LIMAPULUH PEKANBARU - Hasanah, Nurafifa; Alpusari, Mahmud; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to describe the basic skill of teachers in the learning process of IPA at the fifth grade in SDN 11 Pekanbaru city. The method used in this research is descriptive method because the researcher describes objectively and factually about basic skill of learning teachers in the process of IPA learning based on reality in the field. The research is took place at SDN 11 Pekanbaru city which is carried out from July 20th to 25th of August 2016. The data collecting technique used is measurable observation and unmeasurable interview. The instruments used for this research is observation guidline, interview guideline and recorder tools with 2 teachers as a research subject. The results showed the average value obtained on the questioning skills of Va classroom teachers is 66,64; skill of provide reinforcement 66,64; 70,83 of held a variety of skill; skill of explaining 80,94: opening and closing lessons skill  55,5; skill of guiding a small group of discussions 0; 85,7 of classroom management skill; and teaching skill for small group and individual 55,5. Whilst the average value obtained on the questioning skills of Vb classroom teachers is 75,74; skill of provide reinforcement 78,77; 91,67 of held a variety of skill; skill of explaining 90,47; opening and closing lesson skill 74; skill of guiding a small group discussions 0; 85,7 of classroom management skill; and teaching skill for small group and individual 81,4. Based on result of basic teaching skill research for teachers at fifth grade in the learning process of IPA was a good categories.